From Public Funding to Public Investment in Research: A Study of Research Funding Policies and their Impact through two Research Assessment Campaigns in the United Kingdom - Marie-Agnès Détourbe (Revue LISA)
In the United Kingdom, academic research is assessed every five to six years through Research Assessment Exercises (RAEs), the first of which was launched under Margaret Thatcher in 1986 as part of a new policy of quality-related funding. Their results are used as a basis for calculating the recurrent research grants allocated to higher education institutions by the funding councils within the global higher education public budget. Drawing on Louise Morley’s theory (2004) according to which institutional quality mechanisms can be said to be part of a “political technology” conveying certain ideologies, this paper explores the evolution of research funding policies in the United Kingdom from the perspective of research assessment campaigns : it is argued that the definitions, working methods and criteria for research quality assessment have allowed the State to promote a certain vision of research and influenced academic research practices in British higher education institutions in the long run.